Occupational Determinants of Professional Union Membership - White, Frank (Relations industrielles / Industrial Relations)

(untitled) (Département des relations industrielles de l'Université Laval, 1997)
Empirical studies of union membership usually group all professionals together in one occupational category. This study uses a simultaneous equations approach to analyze the union or collective bargaining association membership status of a sample of 9,417 employed Canadian professionals and managers from 16 different occupational groups. The results support the hypothesis that there are significant differences among professions in the probability of their members being in unions or collective bargaining associations. The relative differences are explicable in terms of the characteristics of the professions concerned.